Apropiación y destino de los niños indígenas capturados en la campaña del desierto: Mendoza, 1878-1889 - Diego Escolar (Centre de Recherches sur les Mondes Américains, 2018)
This paper is about the children taken prisoner during the military campaigns for the occupation by the Argentinian State of indigenous territories in the Pampa and Patagonia regions, and then distributed as slaves during the consolidation of the modern liberal state in Argentina. Taking the parish books of baptisms of the period (1878-1889) in the province of Mendoza, we address issues not very well known to the present: a demographic reconstruction of the children distributed in the province, the crisis of ethnic and racial classification caused by their impact, the procedures of contradictory formalization of the illegal appropriation, and their “incorporation with exception” to the everyday social relations and spaces.